Monitoring greenhouse gas emissions through sensors in the cement industry: a review - Oliveira, Mariana de; Oliveira, Guilherme Vieira de; Moura, Bruno Furtado (Brazilian Journal of Production Engineering, 2023)
The importance of sustainability and circular economy in the cement industry has grown in the face of climate change and natural resource scarcity. This industry is responsible for a significant share of carbon dioxide emissions, ranking as the third-largest global emitter. The adoption of clean technologies and the implementation of sensors in the cement industry are crucial for reducing greenhouse gas emissions. They enable production planning, waste reduction, and product quality improvement by providing accurate estimates of difficult-to-measure variables. This empowers companies to make informed decisions and maximize operational efficiency. The methodology adopted in this study was a systematic literature review that addressed the application of sensors in the cement industry, focusing on greenhouse gas monitoring as well as circular economy and sustainability practices. The aim was to analyze the importance and benefits of sensor implementation in the cement industry, identifying advancements, challenges, and trends. It was concluded that sensor implementation in the cement industry is necessary for transforming the production process, promoting sustainability and operational efficiency, and contributing to resource preservation, energy efficiency, and decarbonization.
Keywords: circular economy; cement industry; emissions; sensors